Kiwis on Kiwis: Review of Annie Potts, Philip Armstrong, and Deidre Brown, A New Zealand Book of Beasts: Animals in Our Culture, History and Everyday Life - McHugh, Susan (Humanimalia, 2014)
Annie Potts, Philip Armstrong, and Deidre Brown, A New Zealand Book of Beasts: Animals in Our Culture, History and Everyday Life. Auckland: Auckland University Press, 2013. 288 pp. 49.99 pb.